POST-ERUPTIVE NON-CARIOUS DENTAL LESIONS: CLINICAL FEATURES AND DIFFERENTIAL DIAGNOSIS (International journal of medical sciences, 2026)
Non-carious lesions developing after tooth eruption represent a common group of dental conditions frequently encountered in clinical practice; however, they are often underestimated or misinterpreted at early stages. These disorders are characterized by the loss of hard dental tissues not related to dental caries and are associated with the progressive destruction of enamel and dentin under the influence of mechanical, chemical, or biomechanical factors. The clinical significance of non-carious lesions lies in their tendency to cause increased tooth sensitivity, aesthetic defects, alterations in tooth morphology, dentin exposure, and subsequent secondary complications. Moreover, non-carious processes may clinically mimic dental caries, pulpitis, periodontitis, as well as enamel–dentin pathologies associated with endocrine or gastroenterological diseases, thereby complicating differential diagnosis. This article provides a clinical analysis of the most common post-eruptive non-carious lesions, including enamel erosion, abfraction, abrasion, attrition, wedge-shaped defects, hypoplasia, and pathological disturbances of enamel mineralization. For each condition, etiopathogenetic factors, clinical manifestations, diagnostic criteria, and distinguishing features from dental caries and other hard tissue defects are discussed. In addition, modern diagnostic approaches used in contemporary dentistry are reviewed, with emphasis on the diagnostic value of comprehensive history taking, clinical examination, and instrumental assessment methods (transillumination, radiological evaluation, and index-based analysis), as well as evidence-based individualized therapeutic strategies. The present article is intended to support dentists, residents in restorative dentistry, and practicing clinicians in improving differential diagnostic skills and developing early detection strategies in routine clinical practice.